The Problem of Englishness, Modernism, and Gender—The Critical Reception of Virginia Woolf in Hungary - Séllei, Nóra (FOCUS: Papers in English Literary and Cultural Studies, 2024)
In the English-speaking world, Virginia Woolf has been considered a female modernist for about three decades. Both attributes are crucial: her modernism (which is not a novelty) and the reference to her gendered positioning within apparently “unmarked,” but as it transpires after a careful scrutiny, rather male modernism. The question is whether her critical reception in Hungary follows the tendencies in EnglishAmerican criticism, and if not, where that difference is rooted, and what reasons can be discovered for that difference. These questions are all the more urgent as ninetythree years after the publication of her first novel (1915) and sixty-seven years after her death and the posthumous publication of her last novel (both in 1941), all her major works are available in Hungarian translation: all her novels, her two seminal feminist essays A Room o f One ’s Own and Three Guineas, two short stories (“Mark on the Wall” and “The Legacy”), thirty-three shorter essays in the volume A pille halála (the title is a translation of her essay and volume title The Death o f the Moth) and most of the texts from her autobiographical writings Moments o f Being, even though the bulk of her letters and diaries is still missing. So at this moment, it seems worth taking a glimpse of how her oeuvre has been contextualised in Hungary,1 both in professional terms and in the eyes of the reading public.